Injuries and illnesses in Swedish Paralympic athletes - A 52-week prospective study of incidence and risk factors - Fagher, K.; Dahlström, Ö.; Jacobsson, J.; Timpka, T.; Lexell, J. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Introduction: Sports-related injuries and illnesses in Paralympic sport (SRIIPS) are a concern, but knowledge about the etiology and risk factors is limited. The aim of this study was to describe the annual incidence, type, and severity of injuries and illnesses among Swedish Paralympic athletes and to assess risk factors. Methods: Swedish Paralympic athletes (n = 107) self-reported SRIIPS every week during 52 weeks using an eHealth application. Incidence proportions (IP) and incidence rates (IR) were used as measures of disease burden. Time-to-event methods (Kaplan-Meier and Cox regression) were used to identify risk factors. Results: The annual IP for injury was 68% and for illness 77%. The injury IR was 6.9/1000 hours and the illness IR 9.3/1000 hours. The median time to injury was 19 weeks (95% CI: 10.5-27.4) and to illness 9 weeks (95% CI: 1.4-16.6). Most injuries occurred during training, and 34% were classified as severe (=21 days of time loss). An increased injury risk was observed among athletes in team sports (HR 1.88; 95% CI: 1.19-2.99), athletes with a previous severe injury (HR 2.37; 95% CI: 1.47-3.83), and male athletes (HR 1.76; 95% CI: 1.06-2.93). The most common illness type was infection (84%). Athletes in team sports (HR 1.64; 95% CI: 1.05-2.54) and males with a previous illness (HR = 2.13; 95% CI: 1.04-4.36) had a higher illness risk. Conclusion: Paralympic athletes report a high incidence of injuries and illnesses over time. This emphasizes the need to develop preventive strategies of SRIIPS and optimize medical services for this heterogeneous athlete population.